Comparative Studies of MgFe\(_2\)O\(_4\) Nanoparticles Synthesized using Different Precursors by Sol Gel Auto Combustion Method - Upadhyay, Shiva; Sreenivas, K. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2015)
Nanostructured powder of MgFe\(_2\)O\(_4\) was prepared by sol gel auto combustion method using two different precursors. It is an ultimate combination of slow and sustained gel formation and subsequent combustion. In this work, our aim is to synthesize nanoparticles of MgFe\(_2\)O\(_4\) using different precursors and to compare their relative characteristics and also to investigate that which combinations have result in better properties. The precursors of the solid were obtained from different gels of metal nitrates and metal nitrate, metal acetate with glycine used as an oxidizer and a fuel having pH value of 2 and 6, respectively. During our keenly observed processing, it was reproducibly noted that in the case of acetate-nitrate gel the self-propagation temperature was approximately 120\(^°\)C-130\(^°\)C while in the case of nitrate-nitrate gel the self-propagation temperature was approximately 180\(^°\)C-200\(^°\)C. The crystal structure, shape and grain size of the nanoparticles had been compared by XRD, SEM and TEM. VSM was used to investigate the magnetic properties of obtained powder. The hysteresis curves indicated the ferromagnetic behavior of the samples at room temperature. FTIR supports the absorption value of octahedral and tetrahedral sites.